Есть ли в фауне СССР ящурка ордосская — Eremias brenchleyi Gunter, 1872 (Sauna, Reptilia)? - Щербак, Н.Н. (Вестник зоологии, 1975)
The position of the suborbital scutellum relative to the mouth edge as it is exemplified by Eremias multiocellata is not connected correlatively with the diagnostic characters for E. argus and E. brenchleyi. That is why the latter form ought to be considered a species. Examination of a single specimen of E. brenchleyi from Buryatia showed that this specimen cannot be related unconditionally to the given species. Probably it could be a mistake in the label (such cases had already taken place in the Kyakhta museum). Everything above-mentioned does not permit E. brenchleyi to be included into a list of species of the USSR fauna.